Carbon stock in particle size fractions of soil organic matter under different land use systems in the eastern Amazon (Research, Society and Development, 2023)
The study of organic matter in its various compartments, as well as its relationship with the management of the system or land, aims to develop ecosystem strategies for sustainable land use, with a view to reducing the impact of agricultural activities on the environment. The granulometric fractionation allows the study of the most humid and typically more stable compartments to the changes in the soil environment, caused by the handling. The objective of this study was to evaluate and quantify the carbon stock in granulometric fractions of soil organic matter under different systems of use in the Eastern Amazon. The study was carried out in the eastern Amazonia, in the municipality of Igarapé-Açu, in a soil classified as Yellow Latosol. Experimental areas located in the communities of Cumaru (Crossbeam Cumaru), Nova Olinda (on small farmer properties) and UFRA-FEIGA. The systems of use consist of T1 CC (Cumaru Capoeira), T2 CSQT (Cumaru without crushed burning), T3 (SAF Capoeira Plantio), SAF 1 PT (SAF planting crushed), SAF 2 C (SAF Capoeira Plantio), SAF 1 C (SAF Capoeira Plantio), SAF 1 PT SAF Capoeira) SAF 2 QP (SAF burned and planted). Soil samples were collected at depths 0-5, 5-10 and 10-20 cm. The densimetric fractions were separated (free and lightweight occluded) for the determination of carbon contents by combustion in the LECO CHN-S TRUSTEC elemental analyzer. The studied variables were submitted to analysis of variance and the means were compared by the SNK test. The statistical program SISVAR (Ferreira, 2007) was used. The T3 UFC (Ufra capoeira) system presented a higher concentration as a function of the sandy-clay texture of this area, which provided the concentration, the management of the area, without soil rotation, to vegetal residues in the soil from Capoeira, which helps maintain soil organic matter and nutrient cycling. The contribution of the S + A fraction stood out in the concentration and total carbon stock.